Evolutionary Triangulation to Refine Genetic Association Studies of Spontaneous Preterm Birth - Manuck, Tracy A.; Huang, Minjun; Muglia, Louis; Williams, Scott M. (American Journal of Perinatology, 2017)
Objective The objective of this study was to apply evolutionary triangulation, a novel technique exploiting evolutionary differentiation among three populations with variable disease prevalence, to spontaneous preterm birth (PTB) genetic association studies.Study Design Single nucleotide polymorphism (SNP) allele frequency data were obtained from HapMap for CEU, GIH/MEX, and YRI/ASW populations. Evolutionary triangulation SNPs, then genes, were selected according to the overlaps of genetic population differences (CEU = outlier). Evolutionary triangulation genes were then compared with three PTB gene lists: (1) top maternal and fetal genes from a large genome-wide association study of PTB, (2) 640 genes from the database for PTB, and (3) 118 genes from a recent systematic review. Empirical p-values were calculated to determine whether evolutionary triangulation enriched for putative PTB associating genes compared with randomly selected sample genes.Results Evolutionary triangulation identified 5/17 maternal genes and 8/16 fetal genes from PTB gene list 1. From list 2, 79/640 were identified by CEU_GIH_YRI evolutionary triangulation, and 57/640 were identified by CEU_ASW_MEX evolutionary triangulation. Finally, 20/118 genes were identified by evolutionary triangulation from gene list 3. For all analyses, p < 0.001 except CEU_ASW_MEX analysis of list 3 where p = 0.002.Conclusion Genes identified in prior PTB association studies confirmed by evolutionary triangulation should be prioritized for further genetic prematurity research.
Keywords: preterm birth; evolutionary triangulation; genetic; susceptibility; racial disparity